(untitled) (Fiep Bulletin - online, 2011)
The university extension allows to the exchange of experiences and the production of the knowledge practical technician and, based in the necessities presented for the proper community. In this transforming relation between university and society, we elect the promotion to health as main dimension of orientation, searching to modify the life conditions, in worthy and adjusted way, beyond pointing with respect to transformation of the individual processes of taking of decisions, favouring the quality of life, health and sexuality. The aim of this work was to guide the adolescent participants how much to the biopsychosocial transformations of this period, extending the agreement of the sexuality and making possible reflections on it, contributing in the development of attitudes responsible to the exercise of the citizenship, one better quality of life and, still, standing out actions come back to the auto-support. This research presents qualitative boarding and for the study and development of the activities we follow the "Itinerary of Research" of Paulo Freire. The results and discussion were organized in accordance with the profile of the participants, generating subjects, codification and critical unveiled of each generating subject. The generating subjects were: puberty; anatomy of the feminine and masculine sexual agencies, menstrual cycle and referring terminologies to the sexuality. Through the experiences told for the group, the extension had contributed with its scientific knowledge, which were confronted with its experiences, extending the knowledge of all the involved ones. The experiences were valid in the process of education and learning of the participant academics and in the stimulus of the critical conscience of the subject participants, assisting in the taking of decisions, the communication and the leadership.